Pemilihan Kode Pada Generasi Muda Non-Jawa - Suharyo, Suharyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This study aims to reveal the selection of code among the non-Javanese young generation. This is based on the many local language defense symptoms increasingly fragile. To answer the anxiety,  in this study used a questionnaire technique to get the data distributed to 45 respondents, data analysis using simple percentage techniques and interpretation methods. The result, (a) the younger generation who use Indonesian as every day language in the realm of home (44.44%), using local languages (55.55%),  (b) the language used with friends as much as (55.55%), using the Indonesian language and using the local language as much (44.44%), (c) languages used in older friends (77.78%)  using Indonesian language and using local languages (22.22%), (d) respondents strongly agree (22.22%) that Indonesian language is more important than local languages, (55.56%) answered agree, and the rest (22.22%) answered disagree.